The Influence of Organic and Inorganic Amendments on Phosphorus Chemistry in Two Acidic Soils of Southwestern Ghana - Victor, Owusu-Gyimah; Klogo, Phanuel Yao; Gbefo, Francis (UNIVERSITY OF LAMPUNG, 2025)
A study in southwestern Ghana compared the effects of organic and inorganic additives on P availability and related factors in two acidic soils, Ankasa and Abenia. Different amounts of P as KH2PO4 were applied: 0.067 g kg-1 for Abenia and 0.041 g kg-1 for Ankasa. Soil samples were treated with cow dung, Chromolaena odorata, and poultry droppings for six weeks to increase standard P requirement and neutralize exchangeable Aluminum. Data analysis was performed using GenStat (version 14). An analysis of variance (ANOVA) was conducted for the soil amendments, followed by Tukey’s comparison test at a 5% significance level to identify significant differences among the soil amendments. The result showed that higher rates of organic amendments significantly increased pH, available P (Bray 1 and NaHCO3-P), NaOH-P, and reduced exchangeable Al concentration. Poultry droppings and cow dung impact notably improved soil quality. At the same time, CaCO3 had similar effects on soil pH. However, it did not significantly affect P availability or NaOH-extractable P. CaSO4 and CaCO3 had minimal impact on phosphorus distribution, suggesting that altering pH or exchangeable Al does not necessarily change P fractions. Poultry droppings, rich in P, could be a potential alternative to lime in enhancing P availability and reducing soil acidity.